Cultural Analysis of the Perfumery Business - Velinov, Ivo Iv. (Economy and Business Yearbook, 2022)
The research aims to examine the perfumery business. It is organised in three directions: luxury product and consumer, authorised selective distribution channel and geographical distribution. The conducted interviews among the Bulgarian consumers determine the direction of data collection for the perfumery business in a Bulgarian city. Data analysis presents a survey of the qualitative typology of the consumer expectations in the aesthetics.